Peningkatan Kesadaran Cinta, Bangga, dan Paham (CBP) Rupiah Bagi Masyarakat Pedesaan : Pengabdian - Mardia, Seliy; Simanjuntak, Anggie Armitha; Pratama, Fahrezi Aryuda; Andrean, Devri; Meutianingrum, Farah J. (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Love, Pride, and Understanding of the Rupiah (CBP Rupiah) socialization is one of Bank Indonesia's program to strengthen financial literacy and encourage positive public attitudes towards the national currency. This community service (PKM) activity aims to provide education and increase understanding of the CBP Rupiah among residents of Mulyorejo, Limbung Village, especially productive-age mothers. The socialization was carried out at the Kenanga Integrated Health Post (Posyandu) using a participatory approach through interactive lectures, practical simulations, and a question-and-answer session. The participants numbered 48 people, consisting of housewives at productive age. The material presented included an introduction to the characteristics of authentic rupiah, how to care for money, the dangers of counterfeit money circulation, and an introduction to safe non-cash transactions. This activity is expected to foster the habit of recognizing and protecting rupiah among the community, as well as raising awareness of the importance of safe transactions.